Inverse Association Between the Mediterranean Diet and COVID-19 Risk in Lebanon: A Case-Control Study - El Khoury, Christine N.; Julien, Sofi G. (Frontiers in Nutrition, 2021)
Background: Since 2019, the world is confronting the COVID-19 public health crisis that deeply impacted all aspects of life, from the health sector to economy. Despite the advancement of research targeting pandemic containment measures, more strategies are still needed to alleviate the burden caused by this novel disease. In particular, optimal nutrition was proposed as a possible mitigating factor in the context of COVID-19. Indeed, the light is shed on balanced diets, such as the Mediterranean diet, which present the finest nutritional quality to support the immune system and other physiologic functions. In contrast, less varied diets that lack the needed nutrients and favor inflammation have been correlated with adverse health effects, including a hindered immune response, such as the western diet. Methods: This observational case control study aimed at exploring the possible associations between the different dietary patterns present among a sample of the Lebanese population and the COVID-19 occurrence and outcomes. An online survey collected information about the sociodemographic characteristics, health status, lifestyle and dietary habits through Mediterranean diet questionnaire and a semi-quantitative food frequency questionnaire, and the COVID-19 infection and its burden. The sample consisted of 399 respondents divided into the case and control groups (37.6% and 62.4%, respectively) on the basis of the presence or absence of a COVID-19 infection history. Results: The participants in the case and control groups had average adherence to the Mediterranean diet and their dietary intake was closer to the western diet. However, the cases had a lower mean of the MedDiet score (p = 0.009). Food groups consumption analysis showed that this significant difference within the overall similar dietary patterns was due to a higher consumption of poultry and lower intakes of olive oil among the cases. Additionally, gender influenced the levels of different foods’ consumption. Nonetheless, the dietary intake did not impact the COVID-19 burden. Conclusion: Adherence to the Mediterranean diet was significantly associated with a decreased risk of COVID-19. It is recommended to adopt healthy food choices within the different dietary patterns to prevent the infection. These findings should be validated in larger-scale studies.